The Derivation of Crystal Orientation Matrix for Triclinic System on Two-circle Diffractometer - Rammo, N. N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The limited availability of the two-circle diffractometer to collect intensity measurements down to the monoclinic system has been extended in a novel procedure to collect intensities for the triclinic system. The procedure involves the derivation of matrix elements from graphical representation of the reciprocal lattice. Offset of  the origins of  the upper layers from that of the zero-layer - characteristic of triclinic system - is determined and the  3 x 3  matrix elements are evaluated accordingly. Details of  crystal alignment by X-rays for the triclinic system utilizing the intensities of  equivalent reflections is described